Optimization of gas sensitivity of CuO/carbon composites with carbon particles synthesized from acacia auriculiformis branches - C.A. Samarahewa; Sunil Dehipawala; P. Samarasekara (International Journal of Membranes, 2024)
Carbon particles fabricated from the core of acacia tree branches were utilized to synthesize CuO/carbon composite films. The gas sensing properties of these films grown on glass substrates using the doctor blade method were measured in 1000 ppm of methanol vapor at the room temperature. All the films were annealed at 75 0C for 1 hour in air. The structure, the optical band gap and the surface morphology of the samples were determined using XRD patterns, UV-Visible spectrums and SEM micrographs, respectively. The XRD findings suggested that a single phase of CuO might crystallise as thin films. The XRD patterns were used to assess the samples' average crystallite size, strain, and dislocation density. The peaks of carbon were not visible in the XRD patterns of the films with CuO/carbon due to the amorphous nature of carbon. Platelet particles were observed in SEM images of pure carbon samples. Mass ratio between cupric oxide (CuO) and carbon particles was varied to optimize the gas sensitivity. The gas sensitivity of carbon could be enhanced by adding CuO powder. The highest gas sensitivity (1.43) was measured for the film with 90% CuO and 10% carbon particles.
Keywords: Acacia; Cupric oxide; carbon; gas sensitivity; methanol vapor